Pengembangan Sistem Informasi Pencatatan Keuangan Berbasis Web di Dukuh Tegalan - pratiwi, sinta arum; susena, edy; Kusuma, Ridho Surya; Nugroho, Rakhmat Prasetyo Agung; Iriani, latifah; Supriyanto, Joko (SIBER PRESS Universitas SIBERMU, 2025)
Abstract—Financial recording is an important aspect in the administration of an organization or community, including in Dukuh Tegalan, However, until now financial recording in Dukuh Tegalan still uses a manual method using books, which are prone to recording errors, data loss, damage, and failure of efficiency in managing residents’ financial data. This problem can certainly hinder transparency and accountability in financial reporting. To overcome this, a digital-based financial recording information system was designed and develoved using the Waterfall Method. This method was chosen because of its systematic and structured stages, starting from planning, needs analysis, system design, implementation, testing or testing, and maintenance. This information system is designed to facilitate recording of income and expenditure of funds in Dukuh Tegalan, creating financial reports reports automatically and practically, and can store data safely and in an organized manner. Based on the initial hypothesis, it reduces the level of recording errors, and provides convenience in recording and preparing financial reports in real-time and accurately. In addition, this system is expected to be able to increase transparency and citizen trust in financial management at the hamlet level. Keywords—digital based finance; waterfall method; automatic; practical ; real-time